CRYPTOCURRENCY AS DIGITAL ASSETS: FUNCTIONS, CLASSIFICATION AND GLOBAL REGULATORY PRACTICE - KHARUN, Olena; HRYTSYNA, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the essence of cryptocurrencies as a new form of digital assets, their economic and technological status in the modern financial system. Key approaches to defining cryptocurrency are analyzed, and its main characteristics are highlighted – decentralization, transaction irreversibility, lack of an issuer, and programmability. Cryptocurrencies are classified by functional purpose (payment, utilitarian, investment, management, NFT), technological basis (proprietary blockchains, tokens on smart contracts), value stability mechanism (stablecoins versus volatile coins), and level of decentralization.The main functions of cryptocurrencies are considered: a means of circulation, a store of value, a measure of value, and a programmable currency. Advantages are identified – transaction speed, globality, financial inclusion, as well as significant limitations: volatility, legal uncertainty, energy consumption, cybersecurity risks, and illegal use. International approaches to regulating cryptocurrencies are analyzed: from bans in individual countries to flexible regulation, licensing of providers, as well as initiatives to introduce central bank digital currencies (CBDC). Recommendations for Ukraine and developing countries are separately substantiated: it is proposed to improve the legislative framework for digital assets, create a reliable financial and technological infrastructure, increase the financial literacy of the population, as well as introduce mechanisms to protect investors and minimize technical risks. The prospect of further development through the integration of hybrid tokens, CBDC and new forms of digital assets is expressed, which can increase the stability, transparency and efficiency of national and global financial systems.
Keywords: cryptocurrency; digital assets; functions of money; classification of tokens; regulation of digital currencies; CBDC; financial inclusion